Integration of Islam and Science in Modern Knowledge Foundations: Integrasi Islam dan Sains dalam Fondasi Perkembangan Ilmu Modern - Saipul wakit; Muhammad Ihsan Dacholfany; Margiyono Suyitno; Anis Fauzi (Halaqa: Islamic Education Journal, 2026)
General Background: Islam as a knowledge-centered religion historically contributes to scientific and technological development through the integration of revelation and rational inquiry. Specific Background: During its golden age, Muslim scholars produced foundational theories, methods, and innovations across disciplines, including mathematics, medicine, and economics, which remain relevant in modern science. Knowledge Gap: Contemporary discourse often positions religion and science as dichotomous, overlooking the integrative epistemology embedded in Islamic intellectual traditions. Aims: This study analyzes the role of Muslim scholars, examines the urgency of science within Islamic perspectives, and identifies supporting factors in scientific advancement. Results: Findings reveal that Islam promotes knowledge without separating religion and science, demonstrated through contributions of scholars such as Sayyidina Ali, Ibn Sina, Al-Khwarizmi, Abu Wafa, and Ibn Khaldun. Their works continue to shape modern scientific concepts and practices. Additionally, scientific progress was supported by cultural assimilation, translation movements, and leadership awareness. Novelty: The study emphasizes an integrated epistemological framework where Qur’anic principles and scientific reasoning coexist as a unified system of knowledge production. Implications: Reinforcing this integration can stimulate renewed scientific development within Muslim societies and support contemporary interdisciplinary research grounded in both revelation and empirical inquiry. Highlights• Unified epistemology links revelation with empirical reasoning in knowledge formation• Classical Muslim scholarship establishes enduring theoretical and conceptual frameworks• Scientific advancement supported by translation, cultural exchange, and intellectual climate KeywordsIslam; Science; Integration; Scholars; Knowledge